2017
DOI: 10.1016/j.pharmthera.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of DUBs in tumor metastasis and apoptosis: Therapeutic implication

Abstract: Malfunction of ubiquitin-proteasome system is tightly linked to tumor formation and tumor metastasis. Targeting the ubiquitin-pathway provides a new strategy for anti-cancer therapy. Despite the parts played by ubiquitin modifiers, removal of ubiquitin from the functional proteins by the deubiquitinating enzymes (DUBs) plays an important role in governing the multiple steps of the metastatic cascade, including local invasion, dissemination, and eventual colonization of the tumor to distant organs. Both deregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 150 publications
1
46
0
Order By: Relevance
“…In contrast, the activation of HH signaling induced by the agonist purmorphamine (PM) results in enhanced USP37 gene expression that in turn stabilizes GLI1 ( Figure 5 A), and impacts on EMT in BCSBs [ 131 ]. These findings confirm the role of HH signaling in the maintenance of stem cells and EMT [ 132 , 133 ] and the implication of DUBs deregulations on these oncogenic processes [ 134 , 135 ]. Indeed, USP37 downregulation attenuates cell invasion and EMT markers expression by suppressing the HH pathway [ 131 ].…”
Section: Oncogenic Dubs Involved In the Regulation Of The Hh Pathwsupporting
confidence: 82%
“…In contrast, the activation of HH signaling induced by the agonist purmorphamine (PM) results in enhanced USP37 gene expression that in turn stabilizes GLI1 ( Figure 5 A), and impacts on EMT in BCSBs [ 131 ]. These findings confirm the role of HH signaling in the maintenance of stem cells and EMT [ 132 , 133 ] and the implication of DUBs deregulations on these oncogenic processes [ 134 , 135 ]. Indeed, USP37 downregulation attenuates cell invasion and EMT markers expression by suppressing the HH pathway [ 131 ].…”
Section: Oncogenic Dubs Involved In the Regulation Of The Hh Pathwsupporting
confidence: 82%
“…Deubiquitinating enzymes (DUBs) can prevent ubiquitin-mediated degradation of target proteins [ 12 ]. Importantly, dysregulated DUBs expression is frequently associated with the tumorigenesis process, specifically cell self-renewal, apoptosis and EMT [ 13 , 14 ]. It has been confirmed that DUBs are essential for the regulation of stem cell-related markers and controlling various steps of metastatic progression, including invasion, dissemination and eventual metastasis to distant organs [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, our research proves that USP15 directly deubiquitinates EIF4A1 to promote wound healing in keratinocytes. Because USP15 harbors druggable enzymatic activity as a member of the DUBs, it is considered a potential therapeutic target with vital clinical applications ( He et al, 2017 ). Recombinant DUBs or DUB-based virus-related therapy could further be applied to accelerate re-epithelialization, whereas small molecule inhibitors that target DUBs may become a promising intervention for cutaneous overhealing-associated diseases, such as hypertrophic scars and keloids ( Lee et al, 2010 ; Piao et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%